ANALISIS MANAJEMEN RESIKO ASURANSI PRATAMA DAN RETIREPLAN(BANCASSURANCE) PERUSAHAAN AIA FINANCIAL PADA BANK BCA (STUDI KASUS BANK BCA KCP KAS RUNGKUT MADYA SURABAYA) - Andri Hermawan; Syifaul Islamiyah; Shafa Aqila; Sonia Maylany; Ida Ayu Nuh Kartini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study aims to analyze risk management in the marketing of bancassurance products, specifically the Pratama and Retireplan insurance products offered by AIA Financial through Bank BCA KCP Kas Rungkut Madya Surabaya. Using a qualitative case study approach, the research identifies various key risks, such as moral hazard, operational, legal, and reputational risks, which potentially affect customer trust. The findings reveal that risk management has been implemented through strict selection procedures for prospective customers and prudent fund management. However, significant challenges arise in educating customers about the Retireplan product, which requires a deep understanding of its long-term benefits. Recommendations include enhancing customer education through agent training, more structured communication, and leveraging digital technology to improve transparency. This study contributes to strengthening risk management practices in bancassurance in Indonesia and improving customer satisfaction and trust in insurance products.